2010
DOI: 10.1088/0953-8984/22/50/505302
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the electronic properties of armchair carbon nanoribbons by a selective boron doping

Abstract: Armchair carbon nanoribbons (ACNRs) substitutionally doped with boron atoms are investigated in the framework of first-principles density functional theory. Different boron-boron arrangements and concentrations are considered in order to simulate possible aggregation patterns, their structural stability and electronic behavior are determined as a function of ribbon size. In agreement with previous studies, our results show that the dopant atoms have in general a preference for edge sites, but specific effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 38 publications
2
9
0
Order By: Relevance
“…The B doping slightly reduces the cohesive energy compared to the pristine ACNRs. As shown elsewhere, 26 this reduction becomes less important when the system size increases. In particular, the energy reduces while the island is nearby the ribbon edge indicating that the formation of the BC 3 island 47 and the substitution on the edges 48,49 are keys to ACNRs stability routes.…”
Section: Resultssupporting
confidence: 59%
See 3 more Smart Citations
“…The B doping slightly reduces the cohesive energy compared to the pristine ACNRs. As shown elsewhere, 26 this reduction becomes less important when the system size increases. In particular, the energy reduces while the island is nearby the ribbon edge indicating that the formation of the BC 3 island 47 and the substitution on the edges 48,49 are keys to ACNRs stability routes.…”
Section: Resultssupporting
confidence: 59%
“…The ACNRs and B-ACNRs electronic properties have been previously studied in our group 26 by using a similar methodology as in the present research. It was found that B-ACNRs with BC 3 island conformations are more stable than random B arrangements.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…2,7 The structural and electronic characteristics of B-and N-doped graphene sheets and GNRs have been studied both experimentally [22][23][24][34][35][36][37] and theoretically. 14,19,28,[38][39][40][41][42][43] However, the interactions between B and N impurities in graphene have not been investigated in detail. Understanding these interactions is important for the development of an accurate theoretical model of substitutionally doped graphene and GNRs.…”
Section: Introductionmentioning
confidence: 99%